2014
DOI: 10.1021/jf402229u
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Phenolic Metabolism inVitis viniferaBerries with13C6-Phenylalanine: Implication of an Unidentified Intermediate Reservoir

Abstract: Understanding the regulation of phenolic compounds in agricultural products has been a topic of great interest. In V. vinifera berries, phenolics are responsible for important sensory and functional characteristics. To elucidate the ripening profile of phenolic compounds in Cabernet Sauvignon berries, the stable-isotope tracer l-phenyl-(13)C6-alanine (Phe(13)) was incorporated in situ, and the development of labeled and unlabeled phenolics was tracked in the vineyard at different stages of maturity over two vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
(37 reference statements)
1
4
1
Order By: Relevance
“…Moreover, the total anthocyanin content in grape skins under urea treatment was the highest, which was similar to Javier et al., ( 2017 ). However, this result is in contrast with the research results of Chassy et al., ( 2014 ). Due to different vineyard environmental factors and cultivation management measures, nitrogen types also have different effects on anthocyanins, so the effect of phenylalanine is sometimes better than that of urea (Javier et al., 2017 ; Riccardo et al., 2013 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the total anthocyanin content in grape skins under urea treatment was the highest, which was similar to Javier et al., ( 2017 ). However, this result is in contrast with the research results of Chassy et al., ( 2014 ). Due to different vineyard environmental factors and cultivation management measures, nitrogen types also have different effects on anthocyanins, so the effect of phenylalanine is sometimes better than that of urea (Javier et al., 2017 ; Riccardo et al., 2013 ).…”
Section: Discussioncontrasting
confidence: 99%
“…107 Therefore, nitrogenous fertilizer application may improve the aromatic compounds derived from amino acid metabolism. Moreover, Chassy et al 110 proposed that phenylalanine could be accumulated in grape as an intermediate substrate pool (i.e. phenolamides) and be further metabolized under requirements from different metabolic pathways.…”
Section: Volatile Compositionsmentioning
confidence: 99%
“…Due to the participation of phenylalanine in the biosynthesis pathway of bioactive compounds, phenylalanine is considered a source of grape phenol-derived compounds, including anthocyanins, hydroxy cinnamates, avonols, avan-3ols, tannins, and stilbenes 4 . All of these compounds are synthesized from phenylalanine via the phenylpropanoid pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that phenylalanine is found as an abundant amino acid in grapes and is described in the rst stage of the phenylpropanoid pathway, the precursor of various phenolic compounds 3 . It is well demonstrated that apart from the fact that phenylalanine incorporation into grape berries in uences berry phenolic metabolism, also it is detected as a positive compound for grape and wine aromatic characteristics 4 , respect to these facts, this aromatic amino acid drastically participates in the production of aromatic compounds and particular antioxidant components 5 .…”
Section: Introductionmentioning
confidence: 99%